Nikolai Medtner: music, aesthetics, and contexts - Bitzan, Wendelin; Flamm, Christoph (Studien und Materialien zur Musikwissenschaft, 2021)
This volume is the first scholarly collection in the English language that is fully dedicated to Nikolai Medtner’s (1880–1951) life and work. Its contributions offer a variety of approaches, ranging from analyses and interpretive studies to hermeneutical contexts, and including many insights into his aesthetic thought. The articles explore Medtner’s solo piano music, vocal music, and piano concertos, as well as general aspects of his personal relationships and teaching. Among the authors are scholars and musicians from a variety of countries, applying concepts from Eastern and Western musicology, music theory, and performance studies — just as musical traditions of the East and West are simultaneously represented in Medtner’s music.